Wartime Farm : Rediscovering the Sills and Spirit of World War II - Ginn, Peter; Goodman, Ruth; Langlands, Alex (London Mitchell Beazley, 2012)
During World War Two Britain had to look to the land to provide the produce it had previously shipped in from abroad, meaning huge changes on both the agricultural and domestic scenes. Written by the three presenters who spend a year living on a reconstructed farm from the era, Wartime Farm sets these changes within a historical context and looks at the day-to-day life of that time. Exploring a fascinating chapter in Britain's recent history, we see how our predecessors lived and thrived in difficult conditions with extreme frugality and ingenuity. From growing your own vegetables and keeping chickens in the back yard, to having to 'make do and mend', many of the challenges faced by wartime Britons have resonance today.
Include Color Illustrations and Index.
Rediscovering the Sills and Spirit of World War II.
Keywords: World War (1939-1945) -- Great Britain -- Agriculture